Lattice Poisson-Boltzmann Simulations of Electroosmotic Flows in Charged Anisotropic Porous Media (Communications in Computational Physics, 2007)
This paper presents numerical analysis of electroosmotic flows (EOF) incharged anisotropic porous media using the lattice Poisson-Boltzmann method (LPBM),which combines two sets of lattice evolution methods solving the nonlinear Poissonequation for electric potential distribution and the Navier-Stokes equations for fluidflow respectively. Consistent boundary condition implementations are proposed forsolving both the electrodynamics and the hydrodynamics on a same grid set. Theanisotropic structure effects on EOF characteristics are therefore studied by modelingthe electrically driven flows through ellipse arrays packed in a microchannel whoseshape and orientation angle are used to control the anisotropy of porous media. Theresults show that flow rates increase with the axis length along the external electricfield direction for a certain porosity and decrease with the angle between the semimajor axis and the bulk flow direction when the orientation angle is smaller than π/2.After introducing random factors into the microstructures of porous media, the statistical results of flow rate show that the anisotropy of microstructure decreases thepermeability of EOFs in porous media.